RELATION OF GUIDED IMAGERY RELAXATION TECHNIQUES TO DECREASE THE LEVEL OF ANXIETY ON PER-OPERATION PATIENT ( Mawar Unit Jombang Hospital) - Yussi Kurniyawan; . Hariyono; Ucik Indrawati (STIKES Insan Cendekia Medika Jombang, 2012)
Patient preoperative basically experiencing anxiety before the procedure , where a patient needs to be given relaxation , where the relaxation can be influential for patient preoperative useful to lower the patient's level of anxiety . This study aimed to analyze the effect of guided imagery relaxation techniques to decrease the level of anxiety in patients with preoperative in Mawar ward Jombang general hospital.This kind of research using pre experiment by using one group pretest - posttest design . The sampling technique used was simple random sampling and obtained a sample of 21 respondents. Collecting data in this study using a questionnaire. Data processingediting, coding, scoring, tabulating. Analysis of the data in this study using a statistical test Wilcoxon with software. The independent variable is the relaxation guided imagery while the dependent variable is a decrease in the level of anxiety in patients before surgeryResults showed before being given a guided imagery relaxation 6 (28.57 % ) of respondents have moderate anxiety , 13 ( 61.9 % ) of respondents have severe anxiety and 2 ( 9.52 % ) of respondents who have very severe anxiety . After being given a guided imagery relaxation 5 ( 23.81 % ) of respondents have moderate anxiety , 11 ( 52.38 % ) of respondents have a mild anxiety and 5 ( 23.81 % ) of respondents have normal anxiety . Wilcoxon test results obtained value of p = 0.000 <0.05 then the H1 is acceptedThe conclusion of this study is that there is the influence of guided imagery relaxation techniques to decrease the level of anxiety in Mawar Ward Jombang General Hospital.